Vaccinators' Perception of HPV Vaccination in the Saa Health District of Cameroon - Eposi Haddison; Afizu Tambasho; Gael Kouamen; Randolph Ngwafor (Frontiers Media S.A., 2022)
Introduction: Cervical cancer is the second most prevalent cancer among women in Cameroon. In November 2020, the HPV vaccine was introduced into the expanded programme on immunisation. However, uptake of the vaccine has been slow in the Centre region as opposed to other regions in the country. We therefore sought to describe vaccinators' perception of HPV vaccination in Saa health district.Methods: A self-administered questionnaire with both open-ended and closed questions was used to assess the perception of HPV vaccination among 24 vaccinators from the Saa health district. Quantitative data were summarised as proportions while qualitative data were deductively and inductively coded and thematically analysed.Results: Most vaccinators (75%, n = 18) had a good knowledge about cervical cancer and HPV vaccination. Fourteen (58.3%, n = 14) vaccinators correctly reported the target group, number and spacing of doses for the HPV vaccine. Fourteen (58.3%) vaccinators favoured HPV vaccination while the others (n = 10) were sceptical. Sceptics felt manufacturers hadn't given enough proof of the safety of the vaccine and lacked confidence in government's assessment of the epidemiological situation. The COVID 19 pandemic, fear of infertility and the negative influence of social media were perceived as the main reasons for community hesitancy. Vaccinators criticised health authorities for failing to sensitise the population about the HPV vaccine before its introduction.Conclusion: Vaccinators' perceptions of HPV vaccination may influence the offer of HPV vaccination services. Measures to increase acceptance of HPV vaccination and ownership of the activity among vaccinators have to be put in place.